SABDHÀLAMKARA DALAM SEKAR ALIT: RIMA EUFONI RELIGIUS GEGURITAN SUCITA - Suka Yasa, I Wayan (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana; Vol 18 (2011): March 2011, 2011)
Abstract The domination of vowel sounds a, i, and u within the naratif lyrics of Geguritan Sucita seem to represent that the rhyme is euphonious and match with the characteristic of padalingsa: expresive-religious. The religious aura of the lyrics becomes stronger because of the improvement of consonant ng. Concerning the theological aspect of Hindu, if the vowel a, i, and u are followed by the consonant ng (letter of hamsa), they will become the symbol of the three manifestations of God. The first is Ang, which is the holy letter of Brahma. Then, Ing is the holy letter of Isana (Úiwa or Iúwara), and finally, Ung is the holy letter of Wisnu. Therefore, the rhyme of the GS lyrics can be regarded having euphonious-religious character, and moreover, GS is composed to voice and or to sing about religiosity.